Long range and server inspired internet of smart street lights - Singh, Rajesh; Krishna, Konda Hari; Kumar, Rajesh; Gehlot, Anita; Akram, Shaik Vaseem; Chodhury, Sushabhan; Bisht, Yashwant Singh; Bisht, Kailash; Joshi, Kapil (Institute of Advanced Engineering and Science, 2023)
Currently, the integration of long-range (LoRa) and the internet of things (IoT) has been widely adopted in various applications for real-time monitoring with reliability. These technologies empower us to achieve the goal of the United Nations for the establishment of an inclusive, safe, resilient, and sustainable environment. The automation, monitoring, and controlling of streetlights is a necessary task for the development of smart infrastructure. With the motivation from the above, this study proposed a LoRa and IoT server-based architecture for automation and controlling of streetlights along with sensors. To implement the proposed architecture, the hardware of the sensor node and gateway based on ATMega 328P, 433 MHz LoRa module, and Wi-Fi module is realized. The realized hardware is deployed in the real-time environment and the sensor node can sense the motion of the object and also records the intensity value on the server through internet connectivity.